Distance, Lecture Room or Hybrid? - Or the Shape of Future Education at Universities in View of Pedagogy Students - Stawiak-Ososińskа, М.; Olijnyk, М. (LUMEN Publishing House, 2022)
The paper addresses the important subject of the shape and form of future education at universities in pandemic conditions. The objective of the research with the use of action methods and Edward de Bono’s technique of six thinking hats was to learn about the attitude and opinions of the participants of such teaching (students of pedagogy) after a year's experience of distance education, but also to inspire the respondents to look for innovative and non-standard solutions to improve their studies in the following years. The paper presents their perception of the educational reality in which they had to participate, taking into account their knowledge about the pandemic, emotions accompanying them at this difficult time, pessimistic and optimistic aspects of the situation. It also presents their ideas which could support, replace, or improve the existing forms of e-learning or safe studying in pandemic conditions. The findings of this research clearly demonstrated that students miss direct contact with other people. By “putting on” successive imaginary hats, the participants externalized the needs, wishes, feelings, emotions, and expectations of young people towards education decision-makers. They also provided a clear answer that they wish to return to the university, meet with their peers and lecturers, although at the same time they do not believe it is necessary to attend all courses in a lecture room. In their opinion, teaching in the following years should follow a hybrid model. This paper presents their statements, which may become an inspiration for many higher education decision-makers.
Keywords: distance teaching; universities; students' view